Pengaruh Perubahan Iklim Terhadap Populasi Pesut di Kalimantan Timur - Johansyah Syah (Universitas 17 Agustus 1945 Samarinda, 2011)
PENGARUH PERUBAHAN IKLIM TERHADAP POPULASI PESUT(Orcaela brevirostris) Di KALIMANTAN TIMUREffect of Climate Change on the Fresh-Water Dolphin (Pesut) Population(Orcaela brevirostris) In East KalimantanJohansyahFakultas Pertanian, Jurusan Kehutanan, Universitas PalangkarayaPalangkaraya ABSTRACTGlobal climate change is the dynamics agent of environmental degradation, such as habitat of Mahakam Dolphin (Pesut). The degradation is very dangerous for the continuity of Pesut population life and Pesut is highly sensitive toward changes of such factor. Based on several studies conducted, today is found that population of Pesut until the year 2010 is estimated only 50 individuals, while according to Rasi (2011), it ranged 70-80 individuals. The more reduced number of Pesut population from year to year may fear, thus the extinction of this wildlife species could occurred. Some factor influencing the declining of Pesut population are the destruction of forests, changes of Pesut distribution, decreased water oxygen levels and chemical pollution of rivers.Key words : Pesut, Mahakam, Populasi, Perubahan iklim.